2019
DOI: 10.1111/jan.13954
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of bedside handovers: A multilevel, longitudinal study of effects on nurses and patients

Abstract: Aims To investigate the effectiveness of bedside handovers. For nurses, effects on nurse–patient communication, individualized care, coordination of the care process, job satisfaction, intention to leave, patient participation and work interruptions were measured. For patients, effects on patient activation, individualized care and quality of care were measured. Design This is a longitudinal, controlled, multicentred study on 13 nursing wards in five hospitals. The seven interventional wards consisted of two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The assigned participation task should be communicated appropriately to the patient, have congruity with patients' knowledge of nursing routines and their own implementation capacity, as well as be incorporated into routine care with the consideration of infrastructures and healthcare missions [14,54,55]. It has been suggested that planning and performing nursing care at the patient's bedside can improve patient participation, reduce work interruptions [56], and consequently improve nurses' adherence to safe care guidelines [11].…”
Section: Discussionmentioning
confidence: 99%
“…The assigned participation task should be communicated appropriately to the patient, have congruity with patients' knowledge of nursing routines and their own implementation capacity, as well as be incorporated into routine care with the consideration of infrastructures and healthcare missions [14,54,55]. It has been suggested that planning and performing nursing care at the patient's bedside can improve patient participation, reduce work interruptions [56], and consequently improve nurses' adherence to safe care guidelines [11].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis for hypermobile Ehlers-Danlos syndrome (hEDS) is clinical and considers the presence of criteria ( 6 , 7 ) including a spectrum of phenotypes, ranging from asymptomatic condition, non-syndromic JH, to hEDS, and HSD. In 2019, Copetti et al ( 8 ) explored the clinical ramifications of hEDS and HSD and grouped these conditions into a single phenotype termed hEDS/HSD and considered severity in class distinction.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the efficiency of one type of handover over another (i.e., bedside handover, tape‐recorded handover, verbal handover and written handover) is yet to be established 47 . However, quantitative research measuring bedside handover effectiveness is starting to emerge, showing that while bedside handover influenced nurses' recognition of patient participation, patients did not experience any effects; however, surveys used measured patient empowerment, quality of care and individualized care 48 . Thus, ‘evaluation of patient participation in bedside handover’ is an important factor in our survey because it directly measures outcomes related to patient participation in bedside handover and could assist in building evidence of outcomes.…”
Section: Discussionmentioning
confidence: 99%